The Use of Tic-Tac-Toe Game To Enhance The Eighth-Grade Students’ Vocabulary Achievement - Hijjah, Apriliatul; Tasnim, Zakiyah; Rofiq, Annur (English Education Study Program, 2021)
Vocabulary is the main foundation in communicating or interacting with other people in oral or written form. This classroom action research aimed to improve the eighth-grade students’ vocabulary achievement and their active participation at SMPN 1 Asembagus by using Tic-Tac-Toe game. The data were collected by using observation, a vocabulary achievement test, interview, and documentation. The collected data were analyzed quantitatively by using percentage formula. The result of observation showed that there was an improvement on the students’ active participation from 42% in the pre-cycle to 70% in Cycle 1. The vocabulary achievement test showed that there was an improvement on the students’ vocabulary achievement that was 35% in the pre-cyle to 67% of 31 students in Cycle 1 who got score ≥70 in vocabulary test. In conclusion, the use of Tic-Tac- Toe game in vocabulary learning can improve the students’ vocabulary achievement and their active participation.